“Refugees Welcome”: Analysing Transgressive Stickers along Münster’s Harbour - Kastner, Lena; Spreckelsen, Theresa Sophia; Talhaui, Yasmina (Satura, 2018)
A recent study by the Shell Corporation revealed that students are becoming increasingly interested in political matters. The study makes a connection between this development and a growing disposition towards political actions (“Die Shell Jugendstudie”). This development has also become noticeable in Münster. It is not surprising that in Münster, an international university town, many young people are interested in politics and show action in this domain. This often goes hand in hand with the university environment, where students become more aware of the issues relevant in their local and national contexts, as well as in a globalised world. Along Münster’s harbour, there are many bars and clubs. It is one of the city’s designated party-scenes and many of the publicly visible objects are covered in stickers with a multitude of messages ranging from advertisements to political or moral themes. Therefore, we conducted a study to analyse the potential connection between the number of stickers found in that area and the increasing political interest among young people.